Metode Al-Miftah Lil Ulum dalam Meningkatkan Kemampuan Membaca Kitab Kuning Santri - M. Jamalun Nizar; Wasito (Universitas Islam Tribakti Lirboyo Kediri, 2021)
This research activity is intended to find out how the planning activities, implementation activities and evaluation activities of the Al-Miftah Lil 'Ulum method at the Roudlotut Thohirin Sengon Pringgodani Islamic Boarding School, Bantur Malang. This study uses a descriptive qualitative approach. The results of this study indicate that if the Al-Miftah Lil 'Ulum method is carried out properly according to the plan, it can improve the ability to read the yellow book.